2003
DOI: 10.1111/j.1550-7408.2003.tb00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Cryptosporidiosis in Children in Malawi

Abstract: Few studies have examined the molecular epidemiology of cryptosporidiosis in developing countries. In this study, DNA of 69 microscopy-positive human fecal samples collected from Malawi were examined by multilocus genetic analyses. From 43, 27 and 28 of the samples, the SSU rRNA, 70 kDa heat shock protein (HSP70) and 60 kDa glycoprotein (GP60) genes, respectively, were successfully PCR-amplified. Restriction analysis of the SSU PCR products showed that 41 of the 43 PCR-positive samples had C. hominis and 2 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
90
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 16 publications
9
90
2
Order By: Relevance
“…16 Cryptosporidium hominis was the dominant species identified in our study. High levels of C. hominis are consistent with studies from other developing countries such as Peru, 18 Kenya, 16 India, 14 Malawi, 5,7 and Uganda, 4,15 which indicate that anthroponotic transmission may play a major role in the epidemiology of Cryptosporidium in these areas. A relatively high level of C. parvum was also found in the current study and this finding is in contrast to those of studies from other developing regions where C. parvum infections are generally much lower than that of C. hominis .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…16 Cryptosporidium hominis was the dominant species identified in our study. High levels of C. hominis are consistent with studies from other developing countries such as Peru, 18 Kenya, 16 India, 14 Malawi, 5,7 and Uganda, 4,15 which indicate that anthroponotic transmission may play a major role in the epidemiology of Cryptosporidium in these areas. A relatively high level of C. parvum was also found in the current study and this finding is in contrast to those of studies from other developing regions where C. parvum infections are generally much lower than that of C. hominis .…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, other studies in the tropics have indicated that prevalence of infection is highest in months with the greatest rainfall. [4][5][6][7] However, prevalence was highest during the dry season in Kenya. 16 In Venezuela no seasonal variation was detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations